The potential of Pedagogical Lexicography in English for Specific Purposes courses - Hyppolito, Fernando de Barros [UNESP] (Federal Univ Ceara, 2020)
This paper aims to discuss, from the point of view of Pedagogical Lexicography (PL), a study conducted in an English for Specific Purposes (ESP) course at a language center of a public university in the countryside of the state of Sao Paulo. This paper revisits some previously collected data that had not been observed by the bias of the Lexicon studies. Thus, we deal with the potential of the Lexicography area in specific language courses. This paper is based on the concepts of ESP, new learning technologies and also the theory about PL. We concluded that the execution of two of the theories proposed by LP in ESP courses can have beneficial results for the learners. The first would be to indicate the appropriate dictionary for the learner. The second refers to the use of the Pedagogical Dictionary as an instrument that helps in LE learning.
Keywords: English for Specific Purposes; Use of dictionaries; Pedagogical Lexicology